Seed treatment on germination, vigor and development of wheat - Pereira, Fernando Sartori (2019)
Seed treatment (ST) is an important tool in the management of diseases in the wheat crop, although few products are indicated for this purpose. The research must carry out studies related to the ST effectiveness using different products and the possible phytotoxic effect. The aim of this study was to perform physiological tests on seeds and evaluate the development of two wheat cultivars (BRS Guamirim and TBIO Toruk), submitted to 13 different ST. Germination and vigor were analyzed for each treatment. The treated seeds were also sown to the field, where the field emergence and fresh root and shoot mass were determined. In the germination test, the seeds treated azoxystrobin and Bacillus amyloliquefaciens presented a decrease in the cultivar TBIO Toruk. Vigor analyzes indicated differences between treatments in the two cultivars, and the dimethomorph treatment presented the lowest vigor for TBIO Toruk and azoxystrobin for the BRS Guamirim. The seeds submitted to the Carboxamide A treatment showed seedlings the highest values of fresh root and shoot mass. The results presented allow the selection of products with low or no phytotoxicity for incorporating in wheat disease management.